An assessing framework for the proper allocation of collection and delivery points from the residents' perspective. (December 2022) - Luo, Yuanyuan; Liu, Yanfang; Wu, Zihao; Xing, Lijun
Abstract: Along with the advancement of information technology, the prevalence of e-commerce has promoted the rapid development of the express delivery industry. In relation to this, collection and delivery points (CDPs) have become important places to facilitate convenience for residents. Thus far, the majority of studies focused on the logistic transportation perspective without considering residents' convenience. Therefore, this study proposes an assessing framework of four CDP features from the perspective of residents' convenience, with a focus on Wuhan City. In particular, descriptive statistics and spatial analysis were conducted to analyze patterns of service target, adjacency, accessibility, and agglomeration. In addition, regression analysis was conducted on the indicators of adjacency and accessibility, combined with policy and socioeconomic factors. Through this framework, the overserved and underserved areas in Wuhan City were identified on a community level based on CDP location. Several results were obtained as follows. 1) CDPs mainly serve residents in residential and commercial land and that attended CDPs are farther from the urban area than unattended CDPs. 2) The levels of delivery comfort and delivery efficiency of suburban residents are generally lower than those of downtown residents, while the level of delivery efficiency near colleges and universities is higher. 3) Overserved areas are found in urban locations, while underserved areas are located in suburban locations. Moreover, residents near the edge of city centers enjoy higher CDP accessibility than those located in the center. In terms of age, the accessibility inequity is pronounced in the over 60 age group. 4) The spatial distribution of CDPs is in aggregation, and unattended CDPs are more compact than attended CDPs. 5) Finally, policies and socioeconomic factors have different effects on CDPs' adjacency and accessibility. Overall, these findings may provide a realistic estimation of residents' situation to help private firms design better CDP layouts and create efficient delivery systems as well as to help public authorities develop equal and effective planning policies and strategies related to CDPs. Highlights: Proposes an assessing framework of four CDP features from the perspective of residents' convenience. Investigates an array of policies that could be adopted to the CDP supply-to-demand issues at the community level. Shows a detailed inequity analysis on different age groups based on the CDP supply index and population demand model. Explores the main possible factors that influenced CDPs using the logistic regression model.